Cultural and historical factors influencing the verbalization of aggression in English journalistic texts: a comparative analysis of modern and historical texts - Melnychuk, Natalia; Symaka, Anna (Amazonia Investiga, 2023)
his study is aimed at analysingthe influence of cultural and historical factors on the verbalization of aggression in English journalistic texts. Methods. The work employs the method of analysing lexical units, the grammatical method of analysing aggressive markers, and the method of stylistic text analysis. Mathematical methods of data processing included descriptive average, analysis of optimal values, Cronbach’s alpha. Results. In the first half of the 19th century, there were significant indicators of the use of aggressive vocabulary, in particular the words “attack” and “assault” at about 30% and 25%, respectively. These figures, however, decreased to 25% and 20% during the 21st century. The words “bombard”, “demolish” and “destroy” also showed a decreased frequency of use from the 19th to the 21st century from 20%, 15% and 10% to 15%, 10% and 5% respectively.
Keywords: life writing, verbal aggression, physical aggression, normalization, trivialization, gendered aggression, domestic violence